ا لشحو بىة فى مىزان الخ حظ - ا محمد ا بؤ ا لققا سم (Buletin Al-Turas, 2010)
The objective of this article is to answer one basic question, which is: what are the roles played by the thinkers of Islam in dealing with racism happenings during the period of the Abbasid? This article had chosen al-Jahiz as an example of those who tried to prevent the dangers of racism by explaining its consequences on the reality of Muslim community. This article tries to highlight the views of al-Jahiz and their impact in rejecting the views of racists' groups, which were related to several issues that they tried to manipulate to bring turmoil and unrest to the Muslim community. This article will present several views forwarded by al-Jahiz in regard of the military organization of Abbasid Caliphate. In this case, it is highlighted that racism is not confined to the aspect of language alone, but also include aspects of terminology and politics. Among the main factors clarified in this article are, 1. racism and the origin of its term, 2 the point in time of racism movement, 3. the military organization of the Abbasid Caliphate, 4. the attacks of racists groups towards Arabs and Muslims, 5. al-Jahiz's rejection of the racism attacks, 6. the weapons and evil tactics of the racists' groups.